Nationwide epidemiological survey of idiopathic sudden sensorineural hearing loss in Japan. (10th March 2017) - Kitoh, Ryosuke; Nishio, Shin-ya; Ogawa, Kaoru; Kanzaki, Sho; Hato, Naohito; Sone, Michihiko; Fukuda, Satoshi; Hara, Akira; Ikezono, Tetsuo; Ishikawa, Kotaro; Iwasaki, Satoshi; Kaga, Kimitaka; et al.
Abstract: Objectives: Using a large-scale nationwide survey database, we investigated the epidemiological characteristics for idiopathic SSNHL in Japan. Methods: The subjects for this analysis were patients registered in a Japanese multicentre database between April 2014 and March 2016. A total of 3419 idiopathic SSNHL patients were registered in the database, and the clinical characteristics of the idiopathic SSNHL patients were obtained. Several factors associated with the severity of hearing impairment and prognosis were then investigated. Statistical analysis was performed to clarify the factors associated with the severity of hearing impairment and prognosis. Results: There were significant correlations between the severity of hearing loss and diabetes mellitus, kidney disease, past history of brain infarction, heart disease, age (under 16 years/elderly), and symptoms of vertigo/dizziness. We also analyzed the prognostic factors for idiopathic SSNHL, and found that the severity of hearing loss (Grade 3 or 4), heart disease, aged 65 years or over, time from onset to treatment (over 7 days), and symptoms of vertigo/dizziness were all significantly related to poor prognosis. Conclusion: The present large-scale clinical survey revealed current epidemiological trends for idiopathic sudden sensorineural hearing loss (SSNHL) and various factors associated with the severity of hearing impairment and prognosis.